2022
DOI: 10.7759/cureus.23051
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Components of the Deltoid Ligament (DL): A Cadaveric Study

Abstract: Background: The deltoid ligament (DL) is a strong triangle-shaped ligament with a complex fascicular arrangement. Understanding the morphological and/or functional typing of the DL structure is hindered by a paucity of clear, quantitative, and reproducible data and is further complicated by inconsistent terminology use. The aim of this work was to describe different components of the DL using strict identification criteria.Methods: Thirty embalmed cadaveric ankles of both sides were dissected on all sides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…3 Finally, the deltoid is partially covered by the tibialis posterior tendon, of which the tendon sheath forms a part of the deltoid fibers, covering the posterior and middle part. This is comparable to the peroneal tendon sheath covering the lateral ligaments 7 .…”
Section: Deltoid Ligament Anatomymentioning
confidence: 73%
See 1 more Smart Citation
“…3 Finally, the deltoid is partially covered by the tibialis posterior tendon, of which the tendon sheath forms a part of the deltoid fibers, covering the posterior and middle part. This is comparable to the peroneal tendon sheath covering the lateral ligaments 7 .…”
Section: Deltoid Ligament Anatomymentioning
confidence: 73%
“…3 Finally, the deltoid is partially covered by the tibialis posterior tendon, of which the tendon sheath forms a part of the deltoid fibers, covering the posterior and middle part. This is comparable to the peroneal tendon sheath covering the lateral ligaments 7 .
Figure 1.Schematic depiction of multiple segments of the deltoid ligament. The left figure depicts the deep part of the deltoid ligament.
…”
Section: Deltoid Ligament Anatomymentioning
confidence: 83%
“…The deltoid ligament can be split into superficial and deep components, of which it has been found that the deep, rather than superficial, strata confer mechanical stability. The deep component has a specific and reproducible arrangement of fibers in a distinct three-leaf fan-like pattern consisting of the deep anterior tibio-talar ligament, deep intermediate tibio-talar ligament, and the posterior leaf -the deep posterior tibiotalar ligament [4] (Figure 1). Further anatomical and cadaveric biomechanical studies demonstrated that it was specifically the posterior third fibers or RAD that provide this stability in relation to talar shift, tilt, and rotation [5].…”
Section: Technical Reportmentioning
confidence: 99%